FREQUENCY OF UTI IN PREGNANCY ASSOCIATED WITH PRETERM LABOUR: A CROSS-SECTIONAL STUDY - SHAHZADI , A; AHMAD , F (Biological and Clinical Sciences Research Journal, 2024)
This Cross-Sectional Study aimed to determine how common urinary tract infections (UTIs) are in pregnant women experiencing preterm labour. In addition, the study assessed the standard procedure of routinely doing a urine culture and urinalysis simultaneously in these instances. The study was conducted between September 2022 and August 2023 at the Gynae & Obs Department of GKMC Swabi. The medical records of pregnant patients who were hospitalised at the Gynae & Obs department of GKMC Swabi due to preterm labour were analysed. The study determined the incidence of UTIs in these women. The women were divided into two groups based on their diagnoses upon admission: group 1 had preterm labour/preterm prelabour rupture of membranes (PTL/PPROM), and Group 2 had threatened preterm labour (TPL). Urinalysis and urine culture assessments were performed in these two groups to develop a plan to minimise unnecessary urine cultures. Out of 200 women who had preterm uterine contractions, 4.9% had a UTI. There was no difference in the prevalence of UTI between the two groups of women. 3.5% of the urine samples had a positive culture. Escherichia coli was the most commonly found bacterium in both groups of women. A urine culture with a positive screening rate of 7.2% and 91.2% sensitivity can be used to identify women in the TPL group who should have their urine cultured if an abnormal cell counts or a large presence of bacteria exists in the urine. This method can reduce unnecessary urine cultures. The study found that among pregnant women with preterm labour, the incidence of UTIs was 4.9%, with no statistically significant variation between subgroups. Using certain criteria allows unnecessary urine cultures to be reduced while UTIs in this group are promptly detected.